SAT0242 Carotid Artery Ultrasound in Spondyloarthritis. Atherosclerosis Predicition with a New Risk Scoring System. (9th June 2015) - Alonso Blanco-Morales, E.; Bravo-Ferrer, J.; Rey, R.; Bejerano, C.; Fernández, C.; Oreiro, N.; De Toro, F.; Blanco, F.; Pinto, J.
Abstract : Background: Carotid artery ultrasound (US) is a useful tool to asses subclinical atheromatosis. An increased intima-media thickness (IMT) has been described in patients with Spondiloartritis (SpA), mainly in ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Objectives: To evaluate subclinical atheromatosis in patients with SpA identifying associated risk factors and to design a scoring system that allow us to detect patients with increased risk of developing subclinical atheromatosis. Methods: Observational and cross-sectional study of 100 SpA patients, randomly selected from their follow-up visit (2012-14). Demographic, clinical and laboratory data were collected. IMT was measured in mm with a Kotron Agile probe.IMT >0.9mm or visualization of atheroma plaque was considered positive US (US+). SPSS v21.0 was used for statistical analysis, considering p<0.05 as statistically significant. Results: A total of 100 patients (59 APs and 41 AS) were included, mean age of 47 years (±13); 61% were men. Mean IMT was 0.64mm (±0.16). Eight patients had a GIM >0.9mm and 11 patients had atheroma plaques. A total of 18 patients had US+. Variables associated with increased IMT and US+ are described in table 1 . In the multivariate analysis US+ was associated with elevated serum levels of C-reactive protein, increased waist circumference, increased systolic blood pressure and age >60 years. We design AROSpA (A ge, R eactive C-protein, central O besity, S ex, S ystolic pressure, S core in SpA ) risk score system based on these results. Cut-off points were chosen according to clinical established criteria and optimal likehood ratios in significant COR curve analysis. One point was assigned to each of the following items: Age >60 years, C-reactive protein >1mg/dL, waist circumference >102/88cms (men/women), men sex gender, systolic blood pressure >130 mmHg, and SCORE risk >2%. In the COR curve analysis, AROSpA >4 predicted US+ (sensitivity 100%, specifity 86%, positive likehood ratio (LH+) of 7.1; with an area under the curve (AUC) of 0.899, CI 95% 0.827-0.971, p<0.001). Conclusions: US+ was described in 18% SpA patients and it was associated with increased levels of CRP, waist circumference, blood pressure, age and risk in SCORE chart. AROSpA seems to be a simple, cheap and easy scoring system tool that would allow us to identify patients in whom carotid US should be performed to screening subclinical atherosclerosis with high sensitivity and specificity. These results should be validated in a prospective well-designed study, which we are currently underway. Disclosure of Interest: None declared